Transcriptomic and biochemical analyses reveal wheat drought mitigation by Trichoderma simmonsii and reduced demand for canonical plant stress responses - Ascaso, Julio; Mendoza-Salido, David; Pedrero-Méndez, Alberto; Monte, Enrique; Quijada, Narciso M.; Hermosa, Rosa (Frontiers in Plant Science, 2025)
IntroductionDrought negatively affects production in wheat, an important crop worldwide. Some Trichoderma spp. are of interest for sustainable agriculture. Upon plant root colonization, some strains produce multifaceted benefits for its host, including defence priming against environmental stresses.MethodsHere, we investigated the physiological and biochemical responses of wheat (Triticum aestivum L. cv. Basilio) plants to Trichoderma asperellum T25 and T. simmonsii T137 treatments, applied by mycelium inoculation to plant growth substrate, and subjected to optimal irrigation, water stress (WS), and recovery upon rehydration. WS consisted in removing irrigation for 10 days in 14-day-old plants, and rehydration was performed by optimal irrigation for three days. RNA-sequencing analysis was performed on 24-day-old plants inoculated with T137, under different irrigation conditions, using uninoculated plants as controls.Results and discussionRubisco genes were upregulated in Trichoderma-inoculated plants in comparison with those untreated, independently of the irrigation condition. Under WS, 1,913 differentially expressed genes (DEGs), many of them involved in pathways related to plant stress responses, were associated with the Trichoderma application. Carbohydrate metabolism and photosynthesis were the main functional categories overrepresented of upregulated DEGs when comparing Trichoderma-WS and control-WS plants. Such upregulation was accompanied by downregulation of genes involved in biosynthesis of abscisic acid and osmolytes like proline and trehalose, and non-enzymatic antioxidants, in WS Trichoderma-treated plants. Those results together with a healthy phenotype and reduced hydrogen peroxide, proline and malondialdehyde levels indicate a minimal activation of the WS response in Trichoderma-treated plants. We detected 57 wheat transcription factor genes differentially expressed between Trichoderma-WS and control-WS treatments, with overrepresented members of WRKY, MYB, bHLH, NAC and C2H2 families. Our findings provide valuable insights on the protective effect of Trichoderma in wheat plants against drought, an environmental scenario that is increasing with global warming.